In-line rheological measurements of cement grouts: Effects of water/cement ratio and hydration. (January 2015) - Rahman, Mashuqur; Håkansson, Ulf; Wiklund, Johan
Highlights: A novel non-invasive ultrasound sensor unit was used and tested. Change of the shape of the velocity profile was observed and visualized. Change of the rheological properties with concentration and time was determined. UVP can perform accurate measurement of the velocity at very low flow rate. UVP + PD method can be used to determine the change of the rheological properties. Abstract: The rheological properties of cement based grouts change with water/cement ratio and time, during the course of hydration. For this reason, it is desirable to be able to measure this change continuously, in-line, with a robust instrument during the entire grouting operation in the field. The rheological properties of commonly used cement grouts were determined using the Ultrasound Velocity Profiling combined with the Pressure Difference (UVP + PD) method. A non-model approach was used that directly provides the properties, and the results were compared with the properties obtained using the Bingham and Herschel–Bulkley rheological models. The results show that it is possible to determine the rheological properties, as well as variations with concentration and time, with this method. The UVP + PD method has been found to be an effective measuring device for velocity profile visualization, volumetric flow determination and the characteristics of the grout pump used.